2018
DOI: 10.3892/etm.2018.7019
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR‑155 in immune regulation and its relevance in oral lichen planus (Review)

Abstract: Oral lichen planus (OLP) is a chronic mucosal inflammatory disease. The World Health Organization has described it as a potentially malignant condition. The pathogenesis of OLP remains to be fully elucidated, but extensive evidence suggests that immunologic and inflammatory factors have important roles. MicroRNAs (miRs), which are small non-coding RNAs, have been reported to be involved in OLP. In particular, miR-155 is significantly upregulated in patients with OLP. miR-155 has numerous functions and is close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 101 publications
(158 reference statements)
1
19
0
Order By: Relevance
“…The significantly elevated miR155 levels encountered in our study in OLP patients before starting corticosteroid therapy in comparison with controls were in line with former studies recording an upregulated expression of miR-155 in OLP patients 1 . A different study reported an overexpression of miR-155 in peripheral blood monocytes in OLP lesions compared with controls and revealed a close association of its expression with the disease severity 3 . Another study surveyed the erosive type of OLP and identified a positive miR-155-IFN-γ interaction, further enhancing the Th1 mediated immune response in OLP 14 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The significantly elevated miR155 levels encountered in our study in OLP patients before starting corticosteroid therapy in comparison with controls were in line with former studies recording an upregulated expression of miR-155 in OLP patients 1 . A different study reported an overexpression of miR-155 in peripheral blood monocytes in OLP lesions compared with controls and revealed a close association of its expression with the disease severity 3 . Another study surveyed the erosive type of OLP and identified a positive miR-155-IFN-γ interaction, further enhancing the Th1 mediated immune response in OLP 14 .…”
Section: Discussionmentioning
confidence: 96%
“…The association of miRNAs with OLP has been previously reviewed, and a close association was revealed between miR-155 and cytokines linked with OLP, making it a perfect research nominee in OLP 10 . A positive relation was recognized between IFN-γ and miR-155, resulting in a Th1-mediated immune response in OLP 3 . Moreover, it has been proposed that miR-155 is involved in T cells differentiation toward Th1 via IFN-γ signaling.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“… 11 In addition, several miRNAs have been detected to be aberrantly expressed in OLP cases, such as miR-155, miR-27b, and so on. 12 , 13 MiR-23a-3p is a member of the miR-23a-27a-24-2 cluster, it has been suggested to exert its biological functions in different cancers through regulating cellular activation, cell motility and immune cell infiltration. 14 , 15 In a study reported by Chen et al, miR-23a-3p was identified to be downregulated in the tissues of oral squamous cell carcinomas (OSCCs) patients, and overexpression of miR-23a-3p was suggested to suppress tumor proliferation and invasion of OSCC.…”
Section: Introductionmentioning
confidence: 99%